2009
DOI: 10.1021/jp904061q
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of OOH Radical with β-Carotene, Lycopene, and Torulene: Hydrogen Atom Transfer and Adduct Formation Mechanisms

Abstract: The relative free radical scavenging activity of beta-carotene, lycopene, and torulene toward OOH radicals has been studied using density functional theory. Hydrogen atom transfer (HAT) and radical adduct formation (RAF) mechanisms have been considered. All the possible reaction sites have been included in the modeling, and detailed branching ratios are reported for the first time. The reactions of hydrocarbon carotenoids (Car) with peroxyl radicals, in both polar and nonpolar environments, are predicted to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 54 publications
1
75
0
2
Order By: Relevance
“…In non-polar environments, the peroxyl-scavenging activity of HTyr was found to be similar to that of carotenes (*10 5 -10 6 M -1 s -1 ) [126] and canolol (6.8 9 10 5 M -1 s -1 ) [127]; higher than that of sinapinic acid (1.7 9 10 4 M -1 s -1 ) [128]; and much higher than that of melatonin (3.1 9 10 2 M -1 s -1 ) [129], caffeine (3.2 9 10 1 M -1 s -1 ) [123], and Tyr (7.1 9 10 2 M -1 s -1 , this work). Moreover, taking into account that the rate constants corresponding to the Á OOH damage to unsaturated fatty acids are in the range 1.18-3.05 9 10 3 M -1 s -1 [130], HTyr is predicted to protect against peroxyl oxidation of lipids, while the protective effects of Tyr are not expected to be significant.…”
Section: Resultsmentioning
confidence: 82%
“…In non-polar environments, the peroxyl-scavenging activity of HTyr was found to be similar to that of carotenes (*10 5 -10 6 M -1 s -1 ) [126] and canolol (6.8 9 10 5 M -1 s -1 ) [127]; higher than that of sinapinic acid (1.7 9 10 4 M -1 s -1 ) [128]; and much higher than that of melatonin (3.1 9 10 2 M -1 s -1 ) [129], caffeine (3.2 9 10 1 M -1 s -1 ) [123], and Tyr (7.1 9 10 2 M -1 s -1 , this work). Moreover, taking into account that the rate constants corresponding to the Á OOH damage to unsaturated fatty acids are in the range 1.18-3.05 9 10 3 M -1 s -1 [130], HTyr is predicted to protect against peroxyl oxidation of lipids, while the protective effects of Tyr are not expected to be significant.…”
Section: Resultsmentioning
confidence: 82%
“…Carotenoids possess a characteristic electron-rich chromophore, which is involved in the AC of these compounds towards different species (Galano & Francisco-Marquez, 2009;Martínez, Stinco, & Mel endez-Martínez, 2014). LYC as an antioxidant has been associated to the possible health benefits derived from the consumption of tomato.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the computational results are expected to interpret the experimental findings and provide theoretical support for the conclusions of the experimental MPB degradation results. In addition, as a approach of cost-effective, convenient, and avoiding the use of animals for toxicological study [22,23], computational approach is frequently adopted to investigate the molecular basis of environmental, chemical, and biological processes [24,25]. To date, no computational study has been reported on the mechanisms and kinetics of MPB degradation using AOPs, as well as the toxicity assessment of its degradation products.…”
Section: Introductionmentioning
confidence: 99%